EFL Teacher’s Code Switching in the Social Emotional Learning Context - Lingga Agustina Suganda; Ismail Petrus; Zuraida Zuraida (Universitas Jambi, Indonesia, 2021)
The use of Indonesian, besides English, in an English as a Foreign Language (EFL) classrooms is common in Indonesia. This case study investigated the code switching used by the EFL teacher in the Social Emotional Learning (SEL) context. It was conducted in the English SEL model class at a secondary school in Indonesia. The data were collected using observation, interview, Social Emotional Competence Questionnaire (SECQ), and a SEL self-reflection tool. The results highlighted that (1) code switching is the medium of instruction used by the EFL teacher to accommodate all the teaching and learning activities in the social-emotional learning context, (2) using code switching in the EFL classroom discourse is one of the teacher social emotional competencies, and (3) code switching has a positive role to build teacher and students’ social-emotional skills. Teachers who code switch can strongly support the growth of academic and social-emotional skills in EFL learning context.